Product Development of Fresh Bread Substituted with Puree Taro Beneng (Xanthosoma undipes K. Koch) as an Alternative Food Source of Fiber in the Elderly - Aini Rahayu,; Fatma Tresno Ingtyas,; Esi Emilia,; Marini Damanik, (Jurnal Sains Boga, 2024)
The purpose of this study was to determine the production of white bread as a substitute for puree taro beneng as a food source of fiber in the elderly. Knowing the acceptability of panelists to plain bread with taro beneng puree substitution 25%, 50% and 75% from the aspect of color, aroma, taste and texture. Knowing the nutritional content (ash content, moisture content, carbohydrate content, fat content, protein content and fiber content). This type of research is experimental research with a Completely Randomized Design (CRD) consisting of 1 control and 3 treatments for formulation development from the number of substitutes for beneng taro puree (Xanthosoma undipes K. Koch), namely: F1 (75% wheat flour: 25% taro puree), F2 (50% wheat flour: 50% taro puree), F3 (25% wheat flour: 75% taro puree). The acceptance test used 30 elderly panelists with a hedonic test (very like, like, somewhat like, don't like, really don't like). The data analysis technique was carried out descriptively and analyzed using the Kruskal Wallis test method and the follow-up test using the Man-Whitney. The research results showed that the best white bread that was most popular with the panelists based on the acceptability test results was the F2 treatment (50% wheat flour: 50% taro puree) with average values ​​for color (3.77), aroma (3.8), taste and texture (4.23). The results of the analysis of nutrient content were 31.79% water content, 1.80% ash content, 49.1 gr carbohydrates, 8.81 gr protein, 9.08 gr fat and 4.51 gr crude fiber.